Divalent ions are potential permeating blockers of the non-selective NaK ion channel: combined QM and MD based investigations. Issue 40 (5th October 2017) - Sadhu, Biswajit; Sundararajan, Mahesh; Bandyopadhyay, Tusar
Abstract : The interplay between the hydration energy barrier and optimum site-selectivity controls the permeation and blocking features of divalent metal ions. Abstract : The bacterial NaK ion channel is distinctly different from other known ion channels due to its inherent non-selective feature. One of the unexplored and rather interesting features is its ability to permeate divalent metal ions (such as Ca 2+ and Ba 2+ ) and not monovalent alkali metal ions. Several intriguing questions about the energetics and structural aspects still remain unanswered. For instance, what causes Ca 2+ to permeate as well as block the selectivity filter (SF) of the NaK ion channel and act as a "permeating blocker"? How and at what energetic cost does another chemical congener, Sr 2+, as well as Ba 2+, a potent blocker of the K + ion channel, permeate through the SF of the NaK ion channel? Finally, how do their translocation energetics differ from those of monovalent ions such as K + ? Here, in an attempt to address these outstanding issues, we elucidate the structure, binding and selectivity of divalent ions (Ca 2+, Sr 2+ and Ba 2+ ) as they permeate through the SF of the NaK ion channel using all-atom molecular dynamics simulations and density functional theory based calculations. We unveil mechanistic insight into this translocation event using well-tempered metadynamics simulations in a polarizable environment using the mean-field model of water and incorporating electronic continuum corrections for ions via charge rescaling. The results show that, akin to K + coordination, Sr 2+ and Ba 2+ bind at the SF in a very similar fashion and remain octa-coordinated at all sites. Interestingly, differing from its local hydration structure, Ca 2+ interacts with eight carbonyls to remain at the middle of the S3 site. Furthermore, the binding of divalent metals at SF binding sites is more favorable than the binding of K + . However, their permeation through the extracellular entrance faces a considerably higher energetic barrier compared to that for K +, which eventually manifests their inherent blocking feature.